The folk theorem with imperfect public information in continuous time - Christoph Frei; Benjamin Bernard (Theoretical Economics, 2016)
We prove a folk theorem for multiplayer games in continuous time when players observe a public signal distorted by Brownian noise. The proof is based on a rigorous foundation for such continuous-time multiplayer games. We study in detail the relation between behaviour and mixed strategies, and the role of public randomization to move continuously across games within the same model.
Keywords: C73; 330; Folk theorem; repeated games; continuous time; imperfect observability